New Challenges for Health Planning: Chile’S National Cancer Plan [Nuevos Retos Para la Planificación en Salud: El Plan Nacional de Cáncer en Chile] - Villalobos-Dintrans, P (Pan American Health Organization, 2020)
This article describes the process of developing Chile’s National Cancer Plan. This process included an initial diagnostic stage in which various stakeholders were called on to provide different perspectives and proposals. Later, the compiled information was systematized and structured by the Ministry of Health in an action plan with detailed initiatives, objectives, and associated indicators. The Plan was developed along five strategic lines that guide all the proposed actions for the next ten years. The objective of the article is to describe the process by which the Plan was developed, in order to draw several lessons that may be useful in the preparation of other similar plans in Chile and in other countries of the Region. The main lessons learned involve the need for clear diagnoses to make evidence-based proposals, and the importance of conducting this type of planning through a participatory process and with an interdisciplinary approach, resulting in sounder proposals and facilitating their validation and sustainability. © 2020 Pan American Health Organization. All rights reserved.